2011
DOI: 10.1001/jama.2011.1435
|View full text |Cite|
|
Sign up to set email alerts
|

Enteral Omega-3 Fatty Acid, γ-Linolenic Acid, and Antioxidant Supplementation in Acute Lung Injury

Abstract: Context The omega-3 (n-3) fatty acids docosahexaenoic acid and eicosapentaenoic acid, along with γ-linolenic acid and antioxidants, may modulate systemic inflammatory response and improve oxygenation and outcomes in patients with acute lung injury. Objective To determine if dietary supplementation of these substances to patients with acute lung injury would increase ventilator-free days to study day 28. Design, Setting, and Participants The OMEGA study, a randomized, double-blind, placebo-controlled, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
400
3
17

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(420 citation statements)
references
References 30 publications
0
400
3
17
Order By: Relevance
“…While in adult population ARDS has shown a clear trend of decrease in mortality over the last decades, these results are not univocally confirmed in pediatric population, as reported with conflicting results in two recent meta-analysis of the literature (103,104). Over the last few years, different RCTs have proposed promising results in terms of ARDS mortality improvement (53,105,106). Unfortunately, this enthusiasm has to be well weighted in sight of the study design (107,108).…”
Section: Ards Mortality-still a Critical Challengementioning
confidence: 99%
“…While in adult population ARDS has shown a clear trend of decrease in mortality over the last decades, these results are not univocally confirmed in pediatric population, as reported with conflicting results in two recent meta-analysis of the literature (103,104). Over the last few years, different RCTs have proposed promising results in terms of ARDS mortality improvement (53,105,106). Unfortunately, this enthusiasm has to be well weighted in sight of the study design (107,108).…”
Section: Ards Mortality-still a Critical Challengementioning
confidence: 99%
“…While large audits including thousands of patients worldwide have shown that in daily practice, calorie and protein administration are well below current recommendations, varying between 1, 200 and 1,450 kcal/day and 0.5-0.8 g/ kg/day of protein [3], strong evidence regarding optimal energy and protein requirements as well as nutrient choices in various ICU conditions is not yet available. Most recent large trials focusing on one specific element of nutritional support, such as increased calories and/or protein, the use of supplemental parenteral nutrition, or high dose pharmaco-nutrients, have given confusing signals, failing to demonstrate any strong advantage [4][5][6][7][8][9]. This may leave the impression that most of the recommendations based on physiology do not lead to improved outcomes.…”
mentioning
confidence: 99%
“…101 Some studies have confirmed benefits of eicosapentaenoic acid (EPA), ␥-linolenic acid (GLA), and antioxidants in patients with acute respiratory distress syndrome (ARDS) or acute lung injury (ALI). 102,103 In contrast, the recently published OMEGA study, 104 a randomized, double-blind, placebo-controlled trial of 272 patients with ALI, showed no benefit in clinical outcome and possible harm with enteral -3 fatty acids, GLA, and antioxidants, compared to an isocaloric control. The study population demonstrated significantly fewer ventilator-free days and more days with diarrhea.…”
Section: Our Approach To Nutrition Support In CCImentioning
confidence: 95%